The Palgrave Handbook of Development Cooperation for Achieving the 2030 Agenda Contested Collaboration - Chaturvedi, Sachin; Janus, Heiner; Klingebiel, Stephan; Li, Xiaoyun; Mello e Souza, André de; Sidiropoulos, Elizabeth; Wehrmann, Dorothea (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access handbook analyses the role of development cooperation in achieving the 2030 Agenda in a global context of 'contested cooperation'. Development actors, including governments providing aid or South-South Cooperation, developing countries, and non-governmental actors (civil society, philanthropy, and businesses) constantly challenge underlying narratives and norms of development. The book explores how reconciling these differences fosters achievement of the Sustainable Development Goals. Sachin Chaturvedi is Director General at the Research and Information System for Developing Countries (RIS), a New Delhi, India-based think tank. Heiner Janus is a researcher in the Inter- and Transnational Cooperation programme at the German Development Institute. Stephan Klingebiel is Chair of the Inter- and Transnational Cooperation programme at the German Development Institute and Senior Lecturer at the University of Marburg, Germany. Xiaoyun Li is Chair Professor at China Agricultural University and Honorary Dean of the China Institute for South-South Cooperation in Agriculture. Prof. Li is the Chair of the Network of Southern Think Tanks and Chair of the China International Development Research Network. André de Mello e Souza is a researcher at the Institute for Applied Economic Research (IPEA), a Brazilian governmental think tank. Elizabeth Sidiropoulos is Chief Executive of the South African Institute of International Affairs. She has co-edited Development Cooperation and Emerging Powers: New Partners or Old Patterns (2012) and Institutional Architecture and Development: Responses from Emerging Powers (2015). Dorothea Wehrmann is a researcher in the Inter- and Transnational Cooperation programme at the German Development Institute.